Pengaruh Literasi Keuangan, Gaya hidup Hedon, Dan Tingkat Pendapatan Terhadap Perilaku Manajemen Keuangan Generasi Milenial - Aldrian Saputra; Jeni Susyanti; Ety Saraswati (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
AbstractThe purpose of this study is to find out and analyze Financial Literacy, Hedon Lifestyle and Income Level on Millennial Generation's Financial Management Behavior. This research is a descriptive quantitative research with data collection technique using a questionnaire. The sample in this study amounted to 114 respondents. The place of this research is the millennial generation in the Klojen area, Malang City. The sampling technique used is purposive sampling method. Processing of primary data using analysis of Statistical Package for Social Science (SPSS) version 25. Techniques with multiple regression analysis method. The results of this study indicate that partially each independent variable has a positive and significant effect on financial management behavior. Keywords : financial literacy, hedon lifestyle, income level and financial management behavior